ANALISIS PENGARUH CELEBRITY ENDORSEMENT TERHADAP CUSTOMER LOYALTY MELALUI IMPULSIVE BUYING DAN BRAND ATTACHMENT PADA KONSUMEN SCARLETT WHITENING - Azwar; Widiastuti; Budi Setiawan (JURNAL MANAJEMEN MOTIVASI, 2026)
This study analyzes the effect of celebrity endorsement on customer loyalty among Scarlett Whitening users, with impulsive buying and brand attachment as mediating variables. A quantitative approach was applied, with data collected through questionnaires distributed to 200 respondents selected by purposive sampling. Data were analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The mediation test showed that impulsive buying was unable to mediate the effect of celebrity endorsement on customer loyalty, whereas brand attachment significantly mediated the effect of celebrity endorsement on customer loyalty. Keywords: Celebrity Endorsement; Impulsive Buying; Brand Attachment; Customer Loyalty